Understanding Teacher's Perspectives in Media Literacy Education as an Empowerment Instrument of Blended Learning in Early Childhood Classroom - Siti Syarah, Erie; Mayuni, Ilza; Dhieni, Nurbiana (Jurnal Pendidikan Usia Dini, 2020)
Teacher's abilities to understand the benefits and use of media literacy play an important role in dealing with children as digital natives. Media literacy education can be an instrument through the use of blended-learning websites to address the challenges of education in the 21st century and learning solutions during and after the Covid-19 pandemic. This study aims to figure the teacher's perspective in understanding media literacy as an instrument for implementing blended-learning in early-childhood classes. Using a qualitative approach, this study combines two types of data. Data collection involved kindergarten teachers, six people as informants who attended the interviews and twenty-six participants who filled out questionnaires. Typological data analysis was used for qualitative data as well as simple statistical analysis to calculate the percentage of teacher perspectives on questionnaires collected the pandemic. The findings show five categories from the teacher's perspective. First, about the ability to carry out website-based blended-learning and the use of technology in classrooms and distance learning is still low. It must be transformed into more creative and innovative one. Encouraging teacher awareness of the importance of media literacy education for teachers as a more effective integrated learning approach, especially in rural or remote areas, to be the second finding. Third, national action is needed to change from traditional to blended-learning culture. Fourth, the high need for strong environmental support, such as related-party policies and competency training is the most important finding in this study. Finally, the need for an increase in the ease of access to technology use from all related parties, because the biggest impact of the Covid-19 pandemic is on ECE, which is closely related to the perspective of teachers on technology. The research implication demands increase in technology systems and connections between educators, parents, institutional managers, and education policy holders, for ECE services in urban areas for disadvantaged children, and all children in rural or remote areas. Keywords: Blended Learning, Early Childhood Classroom, Media Literacy Education References Aktay, S. (2009). The ISTE national educational technology standards and prospective primary school teachers in Turkey. International Journal of Learning, 16(9), 127–138. https://doi.org/10.18848/1447-9494/cgp/v16i09/46607 Arke, E. T., & Primack, B. A. (2009). Quantifying media literacy: Development, reliability, and validity of a new measure. Educational Media International, 46(1), 53–65. https://doi.org/10.1080/09523980902780958 Briquet-Duhazé, S. (2019). Websites Consulted by Future Primary Level Schoolteachers in France: Differences between Students and Trainees. American Journal of Educational Research, 7(7), 471–481. https://doi.org/10.12691/education-7-7-6 Bryan, A., & Volchenkova, K. N. (2016). Blended Learning: Definition, Models, Implications for Higher Education. Bulletin of the South Ural State University Series “Education. Education Sciences,” 8(2), 24–30. https://doi.org/10.14529/ped160204 Cappello, G. (2019). Media Literacy in I taly . The International Encyclopedia of Media Literacy, 1–6. https://doi.org/10.1002/9781118978238.ieml0155 Chan, E. Y. M. (2019). Blended learning dilemma: Teacher education in the confucian heritage culture. Australian Journal of Teacher Education, 44(1), 36–51. https://doi.org/10.14221/ajte.2018v44n1.3 Cherner, T. S., & Curry, K. (2019). Preparing Pre-Service Teachers to Teach Media Literacy: A Response to “Fake News.” Journal of Media Literacy Education, 11(1), 1–31. https://doi.org/10.23860/jmle-2019-11-1-1 Cheung, C. K., & Xu, W. (2016). Integrating Media Literacy Education into the School Curriculum in China: A Case Study of a Primary School. Media Literacy Education in China, 1–179. https://doi.org/10.1007/978-981-10-0045-4 Chou, A. Y., & Chou, D. C. (2011). Course Management Systems and Blended Learning: An Innovative Learning Approach. Decision Sciences Journal OfInnovative Education, 9(3), 463–484. https://doi.org/https://doi.org/10.1111/j.1540-4609.2011.00325.x Crawford, R. (2017). Rethinking teaching and learning pedagogy for education in the twenty-first century: blended learning in music education. Music Education Research, 19(2), 195–213. https://doi.org/10.1080/14613808.2016.1202223 de Abreu, B. (2010). Changing technology: empowering students through media literacy education. New Horizons in Education, 58(3), 26. https://files.eric.ed.gov/fulltext/EJ966657.pdf Domine, V. (2011). Building 21st-Century Teachers: An Intentional Pedagogy of Media Literacy Education. Action in Teacher Education, 33(2), 194–205. https://doi.org/10.1080/01626620.2011.569457 Friesem, E., & Friesem, Y. (2019). Media Literacy Education in the Era of Post-Truth: Paradigm Crisis. In Handbook of Research on Media Literacy Research and Applications Across Disciplines. IGI Global. Huguet, A., Kavanagh, J., Baker, G., & Blumenthal, M. (2019). Exploring Media Literacy Education as a Tool for Mitigating Truth Decay. In Exploring Media Literacy Education as a Tool for Mitigating Truth Decay. https://doi.org/10.7249/rr3050 Kalogiannakis, M., & Papadakis, S. (2019). Evaluating pre-service kindergarten teachers’ intention to adopt and use tablets into teaching practice for natural sciences. International Journal of Mobile Learning and Organisation, 13(1), 113–127. https://doi.org/10.1504/IJMLO.2019.096479 Kennedy, A. B., Schenkelberg, M., Moyer, C., Pate, R., & Saunders, R. P. (2017). Process evaluation of a preschool physical activity intervention using web-based delivery. Evaluation and Program Planning, 60, 24–36. https://doi.org/10.1016/j.evalprogplan.2016.08.022 Kupiainen, R. (2019). Media Literacy in F inland . The International Encyclopedia of Media Literacy, 1–6. https://doi.org/10.1002/9781118978238.ieml0147 Liene, V. (2016). Media Literacy as a Tool in the Agency Empowerment Process. Acta Paedagogica Vilnensia, 58–70. https://doi.org/http://dx.doi.org/10.15388/ActPaed.2016.37 Livingstone, S. (2013). Media Literacy and the Challenge of New Information and Communication Technologies. The Communication Review, 7(March), 86. https://doi.org/https://doi.org/10.1080/10714420490280152 Papadakis, S. (2018). Evaluating pre-service teachers’ acceptance of mobile devices with regards to their age and gender: A case study in Greece. International Journal of Mobile Learning and Organisation, 12(4), 336–352. https://doi.org/10.1504/IJMLO.2018.095130 Papadakis, S., & Kalogiannakis, M. (2017). Mobile educational applications for children. What educators and parents need to know. International Journal of Mobile Learning and Organisation, 11(2), 1. https://doi.org/10.1504/ijmlo.2017.10003925 Papadakis, S., Kalogiannakis, M., & Zaranis, N. (2017). Designing and creating an educational app rubric for preschool teachers. Education and Information Technologies, 22(6), 3147–3165. https://doi.org/10.1007/s10639-017-9579-0 Papadakis, S., Vaiopoulou, J., Kalogiannakis, M., & Stamovlasis, D. (2020). Developing and exploring an evaluation tool for educational apps (E.T.E.A.) targeting kindergarten children. Sustainability (Switzerland), 12(10), 1–10. https://doi.org/10.3390/su12104201 Rasheed, R. A., Kamsin, A., & Abdullah, N. A. (2020). Challenges in the online component of blended learning: A systematic review. Computers and Education, 144(March 2019), 103701. https://doi.org/10.1016/j.compedu.2019.103701 Rasi, P., Vuojärvi, H., & Ruokamo, H. (2019). Media Literacy for All Ages. Journal of Media Literacy Education, 11(2), 1–19. https://doi.org/10.23860/jmle-2019-11-2-1 Redmond, T. (2015). Media Literacy Is Common Sense: Bridging Common Core Standards with the Media Experiences of Digital Learners: Findings from a Case Study Highlight the Benefits of an Integrated Model of Literacy, Thereby Illustrating the Relevance and Accessibility of Me. Middle School Journal, 46(3), 10–17. https://doi.org/10.1080/00940771.2015.11461910 Sabirova, E. G., Fedorova, T. V., & Sandalova, N. N. (2019). Features and advantages of using websites in teaching mathematics (Interactive educational platform UCHI.ru). Eurasia Journal of Mathematics, Science and Technology Education, 15(5). https://doi.org/10.29333/ejmste/108367 Schmidt, H. C. (2019). Media Literacy in Communication Education. The International Encyclopedia of Media Literacy, 1–6. https://doi.org/10.1002/9781118978238.ieml0126 Ustun, A. B., & Tracey, M. W. (2020). An effective way of designing blended learning: A three phase design-based research approach. Education and Information Technologies, 25(3), 1529–1552. https://doi.org/10.1007/s10639-019-09999-9 Valtonen, T., Tedre, M., Mäkitalo, Ka., & Vartiainen, H. (2019). Media Literacy Education in the Age of Machine Learning. Journal of Media Literacy Education, 11(2), 20–36. https://doi.org/10.23860/jmle-2019-11-2-2 Wan, G., & Gut, D. M. (2008). Media use by Chinese and U.S. secondary students: Implications for media literacy education. Theory into Practice, 47(3), 178–185. https://doi.org/10.1080/00405840802153783 Wu, J. H., Tennyson, R. D., & Hsia, T. L. (2010). A study of student satisfaction in a blended e-learning system environment. Computers and Education, 55(1), 155–164. https://doi.org/10.1016/j.compedu.2009.12.012 Yuen, A. H. K. (2011). Exploring Teaching Approaches in Blended Learning. Research & Practice in Technology Enhanced Learning, 6(1), 3–23. https://www.researchgate.net/publication/229000574 Zhang, K., & Bonk, C. J. (2019). Addressing diverse learner preferences and intelligences with emerging technologies: Matching models to online opportunities. Canadian Journal of Learning and Technology, 53(9), 1689–1699. https://doi.org/10.1017/CBO9781107415324.004 Zhang, L., Zhang, H., & Wang, K. (2020). Media Literacy Education and Curriculum Integration: A Literature Review. International Journal of Contemporary Education, 3(1), 55. https://doi.org/10.11114/ijce.v3i1.4769